Genome-Wide Association and Transcriptome Analyses Reveal Candidate Genes Underlying Yield-determining Traits in Brassica napus - Lu, Kun; Peng, Liu; Zhang, Chao; Lu, Junhua; Yang, Bo; Xiao, Zhongchun; Liang, Ying; Xu, Xingfu; Qu, Cunmin; Zhang, Kai; Liu, Liezhao; Zhu, Qinlong; et al. (Frontiers in Plant Science, 2017)
Yield is one of the most important yet complex crop traits. To improve our understanding of the genetic basis of yield establishment, and to identify candidate genes responsible for yield improvement in Brassica napus, we performed genome-wide association studies for seven yield-determing traits (main inflorescence pod number, branch pod number, pod number per plant, seed number per pod, thousand seed weight, main inflorescence yield, and branch yield), using data from 520 diverse B. napus accessions from two different yield environments. In total, we detected 128 significant single nucleotide polymorphisms (SNPs), 93 of which were revealed as novel by integrative analysis. A combination of genome-wide association studies (GWAS) and transcriptome sequencing on 21 haplotype blocks from samples pooled by four extremely high-yielding or low-yielding accessions revealed the differential expression of 14 crucial candiate genes (such as Bna.MYB83, Bna.SPL5, and Bna.ROP3) associated with multiple traits or containing multiple SNPs associated with the same trait. Functional annotation and expression pattern analyses further demonstrated that these 14 candiate genes might be important in developmental processes and biomass accumulation, thus affecting the yield establishment of B. napus. These results provide valuable information for understanding the genetic mechanisms underlying the establishment of high yield in B. napus, and lay the foundation for developing high-yielding B. napus varieties.